THE EFFECT OF ORGANIZATIONAL CULTURE, WORK MOTIVATION, AND JOB SATISFACTION ON THE PERFORMANCE ACCOUNTING TEACHER IN THE SOUTH JAKARTA - Subekti, Elok; Zulaihati, Sri; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of organizational culture, work motivation and jobsatisfaction on the performance of accounting teachers in South Jakarta. The data testingtechnique uses multiple linear regression analysis which produces the equation Ẏ = 3.845 + 0.367X1 +0.322X2 + 0.384X3. The results of the analysis based on the t test and f test show: (1) There is a positiveand significant influence between organizational culture and teacher performance. (2) There is apositive and significant influence between work motivation and teacher performance. (3) There is apositive and significant influence between job satisfaction and teacher performance. (4) There is apositive and significant influence between organizational culture, work motivation and jobsatisfaction on teacher performance. Based on the results of this analysis, it can be concluded that organizational culture, work motivation and job satisfaction simultaneously affect teacher performance.